A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea - Criales, María M.; Lemaitre, Rafael (Zootaxa, 2017)
A new shallow-water species of the stenopodid shrimp genus Odontozona is described based on a specimen collected on a coral reef environment in the San Bernardo Islands, Caribbean coast of Colombia. Odontozona edyli n. sp. can be separated from all other congenerics by a combination of morphological characteristics, most notably the ornate abdomen with a distinct and complex pattern of spines, carinae and grooves, spination of the carapace, length of rostrum, armature of third cheliped, third maxilliped and telson. This new species is more similar to O. arbur and O. sculpticaudata from the Indo-Pacific than to any other species of Odontozona from the western Atlantic. An unreported male specimen of O. striata from Jamaica, Caribbean Sea revealed morphological differences with the female holotype described by Goy (1981), suggesting a possible sexual dimorphism or a high intra-specific variability as reported for some Indo-Pacific Odontozona species.